The American Academy of Health Behavior 2019 Annual Scientific Meeting: "Theory and Applications of Multiple Health Behavior Change" - Mark Reed (New Prairie Press, 2019)
The American Academy of Health Behavior (AAHB) hosted it's 19th Annual Scientific Meeting at the Westin Poinsett in Greenville, SC March 10-13, 2019. The meeting's theme was "Theory and Applications of Multiple Health Behavior Change." This publication describes the meeting theme and includes the refereed abstracts presented at the 2019 Annual Scientific Meeting.